A Systematic Review on Integrating SSI into Science Education: Its Impact on 21st Century Skills (2014-2024) - Sari, Dwi Retno; Saputro, Sulistyo; Sajidan, Sajidan (MID Publisher International, 2025)
The Socio-Scientific Issues (SSI)-based learning approach has been recognized as an effective method in science education to develop students' essential skills. This study aims to explore the impact of SSI learning on six key skills: scientific literacy, critical thinking, problem-solving, social awareness and responsibility, argumentation, and collaborative and communicative skills. This research method uses the PRISMA guideline to review relevant literature. Articles were obtained from the Scopus database with the keywords